Inflammatory bowel disease in Indonesian children - Badriul Hegar; Yovita Ananta; Diah Rini (Paediatrica Indonesiana, 2007)
Inflammatory bowel disease (IBD) is a term usedto describe two disorders associated withgastrointestinal inflammation: Crohn’s disease(CD) and ulcerative colitis (UC). The incidenceof IBD is higher in developed countries, while there isunpublished data of pediatric IBD in Indonesia.Clinical manifestations of IBD vary, consist ofgastrointestinal (such as diarrhea and abdominal pain)and extraintestinal manifestations. Definite diagnosisof IBD is based on endoscopy and histopathology. Themanagement includes pharmacotherapy, nutrition,surgery, and psychotherapy. This disorder has a highrecurrence rate, where CD’s recurrence rate is higherthan UC.1,2